Infanzia e cartoon: alcune riflessioni pedagogiche - Daniela Sarsini (Firenze University Press, 2012)
The paper speaks about cartoons for first childhood (from zero to six years) to identify the educational aspects and to understand if they can promote the cognitive, intuitive, emotional and relational development in this age.